2017
DOI: 10.1080/10799893.2017.1360349
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone-induced ERs suppresses IGFII activation to alleviate Ang II-mediated cardiac hypertrophy

Abstract: Cardiomyopathy involves changes in myocardial ultrastructure and cardiac hypertrophy. Angiotensin II (AngII) has previously been shown to stimulate the expression of IGF-2 and IGF-2R in H9c2 cardiomyoblasts and increase of blood pressure, and cardiac hypertrophy. Estrogen receptors (ERs) exert protective effects, such as anti-hypertrophy in cadiomyocytes. Tanshinone IIA (TSN), a main active ingredient from a Chinese medical herb, Salvia miltiorrhiza Bunge (Danshen), was shown to protect cardiomyocytes hypertro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Studies have shown that CTGF plays an important role in the process of ECM responses. Studies have also shown that CTGF significantly improved left ventricular (LV) systolic and diastolic function in PKCε mice, and slowed the progression of LV dilatation [3]. These studies have shown that CTGF plays an important role in the development of cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that CTGF plays an important role in the process of ECM responses. Studies have also shown that CTGF significantly improved left ventricular (LV) systolic and diastolic function in PKCε mice, and slowed the progression of LV dilatation [3]. These studies have shown that CTGF plays an important role in the development of cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to idiopathic and family hereditary, it is thought to be related to persistent viral infection and autoimmune-induced myocardial damage. The main pathological changes were enlargement of the heart chamber, thinning of the ventricular wall, and often accompanied by mural thrombus [3].…”
Section: Introductionmentioning
confidence: 99%
“…These experiments did not include β-E commonalities in signaling affected by this compound as described in a 2015 report, and it was presented that a natural compound called tanshinone IIA inhibited estrogen receptor-mediated cardiomyocyte hypertrophy through enhancement of Akt phosphorylation, resulting in reduced expression of calcineurin and subsequent suppression of translocation of NF-AT, with consequent inhibition of hypertrophic signaling (Weng et al 2015 ). Interestingly, tanshinone has recently been observed to affect estrogen receptor activity in ways that alleviates angiotensin II-mediated cardiac hypertrophy (Chen et al 2017 ). The convergence of this mechanism with aspects of cardioprotection reported by Haines et al ( 2000 ) led to speculation that β-E, which is structurally very similar to tanshinone IIA, also offered potential for affecting these processes in ways that might ultimately prove valuable in patient treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In case of cardiac hypertrophy in spontaneously hypertensive rats (SHRs), it was demonstrated that TsIIA may inhibit cardiac hypertrophy by inhibiting the cystatin c (Cys-C)/Wingless (Wnt) signaling pathway (Feng et al, 2017). TsIIA also attenuates the Ang II-induced pathological hypertrophy by estrogen receptors (ERs) in H9c2 cardiomyoblast cells (Chen et al, 2017d). Furthermore, it was reported that TsIIA attenuated MI and cardiac fibrosis in rats by inhibiting Toll-like receptor 4 (TLR4)/myeloid differentiation primary response 88 (MyD88)/NF-κB signaling pathway (Wu et al, 2018).…”
Section: The Pharmacological Effects Of Tsiia Sodium Tsiia Sulfonatementioning
confidence: 99%